Seventeen Crises in Western Civilization That Have Arisen Since the Dark Ages: A Cognition Science-Oriented Approach. - Targowski, Andrew (Comparative Civilizations Review)
The purpose of this article is to synthesize those crises in the unfolding of Western civilization that are controlled by human knowledge and wisdom. The methodology is transdisciplinary, utilizing a cognitive science-oriented, big-picture view of civilization and main conflicts. The crises are investigated across three time periods; the Dark Ages (from the fifth to the fourteenth century), Modern Times (from the fifteenth to the twentieth century), and the present century. The findings reveal that today Western civilization faces seventeen significant crises. Knowledge is not sufficient to solve these crises; we need to employ knowledge-based wisdom. This approach presents a new understanding of how wisdom can be employed to lead to sustainable civilization.